Road Performance Analysis Using PCE MC Value 0.17 on Rungkut Madya Road - Maharani Putri Dewanty; Nita Jesika Panjaitan; Shafira Amalia Putri; Mawinda Oktrify Awati; Achmad Dzulfiqar Alfiansyah (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Passenger Car Equivalent (PCE) is a conversion factor from various types of vehicles into passenger car units (pc). The PCE value in the 2014 Indonesian Road Capacity Guidelines called PKJI 2014 has a long period with the present. The purpose of this study is to prove that there is a change in current traffic characteristics with the traffic characteristics described in the PKJI 2014. To prove this, the study was conducted by comparing road performance using the PCE MC value according to the PKJI 2014 with research that has been done previously with the results of PCE MC using the modified average headway time method showing 0.17 results. The location of this research was carried out on the Rungkut Madya road (2/2 UD), Surabaya City, East Java, Indonesia. The results obtained from this study are the use of PCE MC according to the PKJI 2014, resulting in a theoretical speed value close to the actual speed value compared to using modified PCE MC. So that the calculation of the performance of the Rungkut Madya road or other roads with similar characteristics does not require modification of the PCE MC value.